2022
DOI: 10.3390/bs12050147
|View full text |Cite
|
Sign up to set email alerts
|

Aggression in Adolescents: The Role of Mother-Child Attachment and Self-Esteem

Abstract: Every year, adolescents’ aggressive behavior in the world continues to increase, including in Yogyakarta, Indonesia. Teenagers’ aggressive behavior in Yogyakarta leads to criminal acts resulting in physical sacrifices and death. The aggressive behavior of teenagers is known as Klithih. It develops and continues to increase every year, causing public anxiety and concern. This study aimed to examine the role of mother–child attachment and self-esteem against aggression. Aggression, mother’s attachment, and self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 75 publications
0
3
0
2
Order By: Relevance
“…Agresivitas verbal mencakup tindakan menyakiti orang lain melalui penggunaan katakata kasar seperti mencaci, menghina, membentak, dan sejenisnya, sedangkan agresivitas fisik melibatkan tindakan kekerasan fisik, seperti memukul, menendang, menikam, dan menembak (Mufidah et al 2021;Warburton, 2015). Agresivitas verbal paling sering dilakukan dan dialami oleh remaja, perilaku ini berkontribusi terhadap agresi fisik terutama terhadap remaja dengan gangguan emosi (Muarifah et al 2022;Worth et al 2021). Perilaku remaja dikategorikan agresif apabila bertujuan untuk menyakiti orang lain, meskipun upaya yang dilakukan tersebut tidak berhasil (Afdal et al 2020;Tentama 2013;Myers 2012).…”
Section: Pendahuluanunclassified
“…Agresivitas verbal mencakup tindakan menyakiti orang lain melalui penggunaan katakata kasar seperti mencaci, menghina, membentak, dan sejenisnya, sedangkan agresivitas fisik melibatkan tindakan kekerasan fisik, seperti memukul, menendang, menikam, dan menembak (Mufidah et al 2021;Warburton, 2015). Agresivitas verbal paling sering dilakukan dan dialami oleh remaja, perilaku ini berkontribusi terhadap agresi fisik terutama terhadap remaja dengan gangguan emosi (Muarifah et al 2022;Worth et al 2021). Perilaku remaja dikategorikan agresif apabila bertujuan untuk menyakiti orang lain, meskipun upaya yang dilakukan tersebut tidak berhasil (Afdal et al 2020;Tentama 2013;Myers 2012).…”
Section: Pendahuluanunclassified
“…It also affects the economy (shopping, travel, tourism, etc.) [ 1 ] and the mental health of citizens because of the permanent state of insecurity [ 2 ]. Some studies point to alarming data, for example, physical assault is the major cause of mortality among 15–44-year olds around the world [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have studied an increase in violence due to exposure to an environment of violence and aggressiveness, which leads to a tendency to use violence as a tool [ 6 ]. It has also been shown that there is a direct correlation between aggression and a poor maternal relationship or low self-esteem [ 2 ]. Moreover, technologies, such as smartphones, contribute to an increase in violence, as does the consumption of aggressive video games [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In China and around the world, aggressive behavior has always been a hot issue of social concern and a focus issue of psychological research [ 1 , 2 ]. Numerous studies have found that aggressive behavior is extremely destructive and can bring high costs to individuals and society [ 3 ].…”
Section: Introductionmentioning
confidence: 99%